Continuous purification of Candida antarctica lipase B using 3‐membrane adsorber periodic counter‐current chromatography. Issue 7 (30th April 2018) - Brämer, Chantal; Schreiber, Sarah; Scheper, Thomas; Beutel, Sascha
Abstract: Batch chromatography has several disadvantages, such as insufficient utilization of the capacity of the resin, high buffer consumption and discontinuity. Considering the high costs for downstream processing, a continuously working chromatographic system with three membrane adsorber units was designed, tested and put into operation. The basic principle of the setup is periodic counter‐current chromatography (PCCC). The PCCC system was used for capturing and purifying Candida antarctica lipase B (CalB) directly from cell lysate in one single unit operation. The best purification result was achieved by means of anion‐exchange chromatography. The dynamic binding capacity with Sartobind® Q 75 amounted to 4.2 mg (56 g/cm 2 ). After transferring the method to the 3MA‐PCCC, 0.22 g CalB (73 U/mg) were obtained from 0.9 L E. coli lysate within 6 h and a recovery of 80%. Compared to the batch process, the productivity could be increased by 36% and the buffer consumption could be reduced by about 20%. Although the purification of CalB from lysate by means of anion‐exchange chromatography was not selective and quantitative using the 3MA‐PCCC device, it could be shown that the concept of the system was successfully implemented and led to a significant improvement of CalB purification.